PENGARUH PEMBERIAN JUS LIDAH BUAYA TERHADAP KADAR GLUKOSA DARAH PUASA PADA WANITA PREDIABETES - Pertiwi, Putri Sukma; Rahayuningsih, Hesti Murwani (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Prediabetes is a condition which pioneers of DM. Diet management is the effective method to decrease fasting blood glucose (FBG) level. One of plant that correlates decreasing FBG level is Aloe vera. The purpose ofÂ the study was to prove the effects of Aloe vera on FBG level in prediabetes women. Method: This study was quasi experiment with pre test-post test design. The subjects were people in Tlogosari Kulon Semarang who taken by consecutive sampling. Total subjects were 26 people which was divided in 2 groups. The treatment group was given juice Aloe vera 150 gram per day during 14 days and control group was not given juice Aloe vera. FBG level was measured before and after intervention using spectrofotometri method. During intervention, both of group recorded food intake using food record and food recall. Data was analyzed by Independent sample t-test, Mann Whitney test, and Wilcoxon test. Result : The decreasing of FBG level in treatment group was 20.38Â±14.7 (18.92%) mg/dl and control group was 0.38Â±11.12 mg /dl. Statistic analysis showed that there was significant difference at decreasing of FBG level in treatment group and control group. Conclusion : There was significant decreasing FBG level 20.38 mg/dl after given juice Aloe vera 150 gram per day during 14 days.